Use of an In Vitro Skin Parallel Artificial Membrane Assay (Skin-PAMPA) as a Screening Tool to Compare Transdermal Permeability of Model Compound 4-Phenylethyl-Resorcinol Dissolved in Different Solvents - Bálint Sinkó; Vivien Bárdos; Dániel Vesztergombi; Szabina Kádár; Petra Malcsiner; Anne Moustie; Chantal Jouy; Krisztina Takács-Novák; Sebastien Grégoire (Pharmaceutics, 2021)
Absorption through the skin of topically applied chemicals is relevant for both formulation development and safety assessment, especially in the early stages of development. However, the supply of human skin is limited, and the traditional in vitro methods are of low throughput. As an alternative, an artificial membrane-based Skin Parallel Artificial Membrane Permeability Assay (Skin-PAMPA) has been developed to mimic the permeability through the stratum corneum. In this study, this assay was used to measure the permeability of a model compound, 4-phenylethyl-resorcinol (PER), dissolved in 13 different solvents that are commonly used in cosmetic formulation development. The study was performed at concentrations close to the saturated solution of PER in each solvent to investigate the maximum thermodynamic potential of the solvents. The permeability of PER in selected solvents was also measured on ex vivo pig skin for comparison. Pig ear skin is an accepted alternative model of human skin. The permeability coefficient, which is independent of the concentration of the applied solution, showed a good correlation (R2 = 0.844) between the Skin-PAMPA and the pig skin permeation data. Our results support the use of the Skin-PAMPA to screen the suitability of different solvents for non-polar compounds at an early stage of formulation development.